Sistem Pakar Diagnosa Penyakit Tetelo Menggunakan Metode Certainty Factor - Terisia, Vany; Sestri, Ellya; Raihan, Dendi (Jurnal Sistem Informasi (JUSIN), 2022)
In today's technological era, computers are not only used as a tool to complete human work but can also run applications designed to access information quickly. Expert systems are one part of artificial intelligence. An Expert Systems application is an application that transfers expert knowledge to a computer. That way the computer can also solve problems as is usually done by experts. Expert systems have been widely developed in various fields, including the field of animal husbandry. Detection of tetelo disease can use an expert system application. One of them is to detect Tetelo disease. Therefore, breeders can access information about Tetelo disease that is diagnosed with the help of an expert system that uses the Certainty Factor method. The Certainty Factor method serves to determine the degree of certainty of the diagnosis result.